Factors and gender differences in virtual reality adoption in English learning among vocational college students - Yao Ling; Marlissa Omar; Mohamad Sattar Rasul (Intelektual Pustaka Media Utama, 2026)
Virtual reality (VR) has been adopted in the education field, providing students with innovative methods to acquire and practice skills. With the increasing importance of English education in vocational colleges, learning method (LM) should be transformed and improved to enhance learning efficiency. VR is recognized as a valuable tool to improve learning outcomes, yet its application in English education for vocational colleges remains in the early stages. This study investigates the factors affecting VR adoption and examines whether gender difference among students impacts its practical application. Quantitative research method was conducted utilizing questionnaire to examine the factors affecting vocational students’ VR adoption in their English learning. Total 520 vocational students were selected as respondents to complete the questionnaire, and the data were analyzed using descriptive statistics (mean and standard deviation) and inferential statistics (independent sample t-test) to identify the differences between gender. The findings revealed that identified factors moderately influence VR adoption and no significant gender differences regarding the challenges vocational students face when using VR to learn. This study contributes to promoting VR adoption in English learning and helps to stimulate students’ interest in actively using VR, thereby enhancing learning outcomes and driving the transformation of educational methods.